Tribute to Dr Jacques Rogge: muscle activity and fatigue during hiking in Olympic dinghy sailing - Bourgois, J. G.; Dumortier, J.; Callewaert, M.; Celie, B.; Capelli, C.; Sjøgaard, G. (European Journal of Sport Science, 2017)
`A tribute to Dr J. Rogge` aims to systematically review muscle activity and muscle fatigue during sustained submaximal quasi-isometric knee extension exercise (hiking) related to Olympic dinghy sailing as a tribute to Dr Rogge`s merits in the world of sports. Dr Jacques Rogge is not only the former President of the International Olympic Committee, he was also an orthopaedic surgeon and a keen sailor, competing at three Olympic Games. In 1972, in fulfilment of the requirements for the degree of Master in Sports Medicine, he was the first who studied a sailors` muscle activity by means of invasive needle electromyography (EMG) during a specific sailing technique (hiking) on a self-constructed sailing ergometer. Hiking is a bilateral and multi-joint submaximal quasi-isometric movement which dinghy sailors use to optimize boat speed and to prevent the boat from capsizing. Large stresses are generated in the anterior muscles that cross the knee and hip joint, mainly employing the quadriceps at an intensity of 30-40% maximal voluntary contraction (MVC), sometimes exceeding 100% MVC. Better sailing level is partially determined by a lower rate of neuromuscular fatigue during hiking and for ˜60% predicted by a higher maximal isometric quadriceps strength. Although useful in exercise testing, prediction of hiking endurance capacity based on the changes in surface EMG in thigh and trunk muscles during a hiking maintenance task is not reliable. This could probably be explained by the varying exercise intensity and joint angles, and the great number of muscles and joints involved in hiking.